Pengaruh Corporate Social Responsibility, Penghindaran Pajak, dan Kebijakan Dividen terhadap Nilai Perusahaan - Fria Setiono (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2026)
Public companies must maintain sustainability, as it is related to their value. A company's value can be measured by its share price; a higher market price indicates a company's financial performance and investment returns for investors. A phenomenon has been observed in the consumer non-cyclical sector, which experienced declines and fluctuations in value from 2020 to 2024. This phenomenon indicates that falling share prices lead to a decline in company value. This study aims to analyze the influence of Corporate Social Responsibility, Tax Avoidance, and Dividend Policy on Company Value in companies in the Consumer Non-Cyclical sector listed on the Indonesia Stock Exchange during the 2020-2024 period. The study sample consisted of 10 companies with 50 data observations selected using a purposive sampling technique. Data analysis was conducted using panel data regression with the help of EViews 12 software. The results of the study indicate that (1) Corporate Social Responsibility, Tax Avoidance, and Dividend Policy as a whole have an effect on Company Value, (2) Corporate Social Responsibility partially has no effect on Company Value, (3) Tax Avoidance partially has no effect on Company Value, (4) Dividend Policy partially has no effect on Company Value. These findings prove that Corporate Social Responsibility, Tax Avoidance, and Dividend Policy together are able to influence company value, even though each variable does not have an effect on company value.